Does social capital create trust? Evidence from a community of entrepreneurs - Fabio Sabatini (Fondazione Eni Enrico Mattei (FEEM), 2009)
Which kind of social capital fosters the diffusion of development-oriented trust? This paper carries out an empirical investigation into the causal relationships connecting four types of social capital (i.e. bonding, bridging, linking, and corporate), and different forms of trust (knowledge-based trust, social trust, trust towards public services and political institutions), in a community of entrepreneurs located in the Italian industrial district of the Tuscia. Our results suggest that the main factors fostering the diffusion of social trust among entrepreneurs are the perception that the local community is a safe place, and the establishment of corporate ties through professional associations. Trust in people is positively and significantly correlated also to higher levels of satisfaction and confidence in public services. Participation in voluntary organizations does not appear to increase trust in people. Rather, we find evidence of the other way round: interpersonal trust seems to encourage civic engagement.
Keywords: J24; O15; Z13; 330; Trust; Social capital; Safety; Professional associations; Entrepreneurship; Corporate ties; Group and Interpersonal Processes; Social Perception and Cognition